Diet analyses of the pelagic thresher shark, Alopias pelagicus (Lamniformes: Alopiidae), from the Lombok Strait waters, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Alghozali FA, Salsabila R, Gustianto MWD, Putri HMIH, Himawan MR, Yuneni RR, Hatmoro CK, Rezkiani M. 2023. Diet analyses of the pelagic thresher shark, Alopias pelagicus (Lamniformes: Alopiidae), from the Lombok Strait waters, Indonesia. Biodiversitas 24: 3708-3714. The pelagic thresher shark, Alopias pelagicus, is an endangered shark species estimated to be declining in the Pacific and Indian Oceans because of overexploitation, including from target fisheries and bycatch. Despite its importance in providing better information for species management, the ecological aspects of this species are still rarely studied. This study aims to provide information on the feeding ecology of the pelagic thresher sharks from the Lombok Strait. Stomach samples from 178 specimens were sampled from 2020-2021, and 149 stomachs that contained food contents were analyzed for species diet characterization. Prey Species Accumulation Curve slope values are